MENINGKATKAN MOTIVASI DAN HASIL BELAJAR SISWA MATERI BELAR NEGARA MATA PELAJARAN PKN MELALUI STRATEGI PEMBELAJARAN TEAM ASSISTED INDIVIDUALIZATION (TAI) PADA KELAS IX A MTsN BATU BENAWA KABUPATEN HULU SUNGAI TENGAH - Abdi Rahmani (JURNAL SOCIUS, 2015)
The aim of  the research is to describe low score of the students is caused by the lack motivation of the students in studying PKn subject. There could be motivation factor is also influenced by the lack of teaching media and teaching method  used by teacher when she/he is teaching. So far the teaching method used by teacher is lecture method which has one way communication or  teacher centered where students are passive. This condition makes the students feel boring while they are studying.The aim of the research is to investigate the application of cooperative teaching and learning with Team Assisted Individualization (TAI) toward the increase of motivation and learning outcome in  the PKn subject of the MTsN Batu Benawa students Grade IX A in 2014.This research applied action research method with observation method in group discussion. This research has two cycles, each of which contains one meeting.  Qualitative data  is analyzed descriptively; quantitative data is analyzed in percentage.The data analysis result shows that student motivation in studying PKn can be increased. Learning outcome can also be increased. Class mean score has increased in 17 points. In the first cycle, it is found that the student learning outcome is 64 for pre test and 81 for post test.  Class mean score in the second cycle can be increased to 25 point, from 65 to 90. It is a high improvement. Classical learning mastery also increases. It can be seen from post test result. Post test score in the first cycle is 72% and can be increased into 91% in the second cycle.Keywords: learning motivation, learning outcome, Team Assisted Individualization (TAI), teaching strategy